THE EFFECTIVENESS OF PROVIDING HAND WASHING REMINDER ALARM ON HAND HYGIENE COMPLIANCE AMONG HEALTH WORKERS - Masitah, Putri Dewi; Ningrum, Evi Harwiati; Yuliatun, Laily (Caring: Jurnal Pengabdian Masyarakat, 2023)
Based on data on quality indicators, the achievement in the last three months in the Kerinci Room of RSSA Malang is 63% with the standard set at ≥85%. One of the efforts that can be made is to provide an audio-based hand washing reminder alarm device. Giving reminder alarms can affect health workers' hand hygiene compliance. This study aims to determine the effectiveness of giving hand washing reminder alarms on tabgan hygiene compliance in health workers in the Kerinci Room, RSSA Malang. This study used quasy experimental method with one group pretest-posttest. The sampling technique was purposive sampling with a sample of 9 respondents. This community service instrument uses a hand washing audit form. The data were analyzed with the average result before the intervention was 80.6% and after the intervention was 96.4%. These results prove that there is a difference in the average hand hygiene compliance of health workers before and after being given a hand washing reminder alarm, obtained a p value of 0.026. Health workers in the Kerinci Room have hand hygiene compliance including less because the value is less than the predetermined standard. Therefore, efforts need to be made to improve hand hygiene compliance by providing audio-based hand washing reminder alarms.